Hepatic fat, not visceral fat, is associated with gallbladder polyps: A study of 2643 healthy subjects - Lim, Seon Hee; Kim, Donghee; Kang, Jin Hwa; Song, Ji Hyun; Yang, Sun Young; Yim, Jeong Yun; Chung, Su Jin; Kim, Joo Sung; Cho, Sang-Heon (Journal of gastroenterology and hepatology, 2015)
Background and Aim Gallbladder polyps (GBPs) appear to be strongly associated with obesity and metabolic disease. To date, the relationship between GBPs and fatty liver has not been adequately evaluated. The aim of the present study was to investigate whether GBPs are associated with fatty liver, which is an ectopic regional fat deposit, independent of visceral adipose tissue (VAT). Methods A cross‐sectional study using 2643 health checkup subjects (961 patients with GBP and 1682 age‐ and sex‐matched healthy controls) was conducted. The subjects underwent various laboratory tests, abdominal fat computed tomography (CT), and hepatic ultrasonography. Results The mean age of the subjects was 51.4 ± 8.3 years, and 74.1% were male. GBPs were significantly associated with fatty liver. Multivariate regression analysis revealed that GBPs were significantly associated with the presence of fatty liver (odds ratio [OR] 1.23, 95% confidence interval [CI]: 1.02–1.48), and adjusting for the homeostatic metabolic assessment index had little effect on this association (OR 1.23, 95% CI: 1.02–1.48). Additionally, GBPs remained significantly associated with the presence of fatty liver after adjustments for CT‐measured VAT and subcutaneous adipose tissue (OR 1.24, 95% CI: 1.03–1.50). The degree of fatty liver showed an independent (OR 1.37 95% CI: 1.03–1.80) and dose‐dependent relationship (moderate‐severe fatty liver: OR 1.55 95% CI: 1.07–2.23, P for trend = 0.014) with large GBPs (≥ 5 mm). Conclusion Fatty liver, an ectopic regional fat deposit, was found to be closely associated with GBPs independent of known metabolic risk factors, insulin resistance, and CT‐measured VAT, confirming a relevant clinical relationship between the two diseases.